High temperature thermal treatment of Zn-10Nb2O5-10SiO2 crystal coatings on mild steel - A. A. Ayoola; O. S. I. Fayomi; A. P. I. Popoola (Cogent Engineering, 2018)
Surface enhancement of engineering materials is an essential step in improving the service life, mechanical properties and corrosion resistance of any metal. Behavioural effects of SiO2 particulate on the electrodeposition of Zn-Nb2O5 coatings of mild steel were investigated. Bath composition was developed through zinc electrolyte solution to produce ZnNb2O5–SiO2 alloy. The adhesion profile, topography and microstructures of the coated samples were analysed using atomic force micrographs (AFM), and JEOL JSM 6390 scanning electron microscope (SEM) coupled with energy dispersive x-ray analyser (EDS micrographs). Emco-test microhardness tester and MTR 300 dry abrasion rig machines were used for the determination of hardness and wear resistance of the coated samples. Results of the research showed that finer microstructure of the Zn-Nb2O5–SiO2 composites obtained was due majorly to the addition of SiO2 particulate. Also, hardness behaviour and wear resistance of Zn-10Nb2O5 coating increased due to incremental addition of SiO2 particulate (up to 10 wt%).